SimTool-SynBench - Kinz, Marvin (Universität, 2023)
The SimTool is a toolset to simulate soft tissue deformation during resection surgery. The proposed toolset is an assimilation of 3D packages in Python and Unreal Engine 4 (UE4) with Nvidia Flex integration, which make it possible to adapt the dataset for more applications. The SynBench is a synthetic definable object benchmark that includes the ground truth between two point sets as well as various challenges, namely, deformation levels, noise, outlier, and data incompleteness.
Gesehen am 22.11.2023
Keywords: Forschungsdaten; Datenbank